Evaluasi Pembelajaran Pendidikan Agama Islam dan Implikasinya Terhadap Motivasi Belajar Peserta Didik di MTs NU Banat Kudus - Muchammad Chusnuts Tsawab; Uswatun Khasanah; Nor Faelashofa Afrida; Maisyanah Maisyanah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2020)
Learning motivation is a very important aspect as a step to improve students' learning achievement. In this context, educators have a very big role and responsibility in fostering students' learning motivation, which is one of them by providing an evaluation of learning. The aim is to find out whether the evaluation of learning that has been carried out so far is able to significantly influence the motivation to learn MTs NU Banat Kudus students. The study was conducted using a qualitative design with a case study method obtained from the results of the interview. The results showed that the evaluation of learning is able to give a very big influence on the motivation of students in learning. So it can be concluded that the evaluation of learning is an important component of education, because it is very influential on increasing student learning motivation in increasing volume and learning strategies.